Gemälde : die Sammlung - Lentos Kunstmuseum Linz (Linz : Lentos Kunstmuseum Linz, 2003)
Achenbach, Oswald ; Adrian, Marc ; Aduatz, Friedrich ; Ak, Anatol ; Andri, Ferdinand ; Anzinger, Siegfried ; Appel, Karel ; Attersee, Christian Ludwig ; Bak, Imre ; Baumeister, Willi ; Bayer, Herbert ; Beuys, Joseph ; Birkás, Ákos ; Bischof, Peter ; Bischoffshausen, Hans ; Bohatsch, Erwin ; Böhm, Wolfgang ; Brandl, Herbert ; Braun, Theo ; Brehm, Dietmar ; Camesi, Gianfredo ; Chillida, Eduardo ; Christo ; Ciuha, Jose ; Corinth, Lovis ; Dahmen, Karl Fred ; Dahn, Walter ; Dalpra, Mario ; Damisch, Gunter ; Decleva, Mario ; Dobrowsky, Josef ; Dorfer, Oliver ; Egger, Jean ; Egger, Oliver ; Egger-Lienz, Albin ; Eisenschitz, Willy ; Ernst, Wolfgang ; Fabian, Gottfried ; Faistauer, Anton ; Feher, Laszlo ; Feuerbach, Anselm ; Fohn, Emanuel ; Fontana, Corsin ; Forstner, Leopold ; Freise, Johanna ; Friedrich, Caspar David ; Frohner, Adolf ; Fruhmann, Johann ; Funke, Helene ; Gasteiger, Jakob ; Gauthier, Dominique ; Gertsch, Franz ; Glück, Anselm ; Grabmayr, Franz ; Graf, Franz ; Grünwald, Bela Ivanyi ; Gütersloh, Albert Paris ; Hamak, Herbert ; Hanghofer, Wolfgang ; Haring, Keith ; Hauer, Leopold ; Hebenstreit, Manfred ; Hencze, Tamas ; Hofer, Carl ; Hoffmann, Egon ; Hofkunst, Alfred ; Hofmann, Hanspeter ; Hollegha, Wolfgang ; Huber, Ernst ; Huszar, Vilmos ; Jones, Allen ; Joos, Hildegard & Harold ; Kandl, Johanna ; Kassak, Lajos ; Kiraly, Andras ; Klimo, Karoly ; Klimt, Gustav ; Klinger, Max ; Kocherscheidt, Kurt ; Koko, Demeter ; Kokoschka, Oskar ; Kolar, Jiri ; Kolig, Anton ; Koller, Silvia ; Koller-Pinell, Broncia ; Korab, Karl ; Krieg, Dieter ; Lang, Erwin ; Lassnig, Maria ; Lehmden, Anton ; Leitner-Gründberg, R. ; Liebermann, Max ; Lüpertz, Markus ; Lutz, Anton ; Mahringer, Anton ; Mairwöger, Gottfried ; Makart, Hans ; Malfatti, Nino ; Mars, Ton ; etc.
Duits
Collectie Lentos Kunstmuseum Linz
boek